Building future standard and Knowledge Management for Inventory Management in Logistics Europe Central - Oravcová, Lucia (2015)
The aim of this master thesis is to build standards and Knowledge Management for the Inventory Management in the Materials Management department in the Logistics Europe Central region. The theoretical of this master thesis part provides a theoretical basis in Lean management with the focus on administrative environment. It further clarifies the importance and benefits of standards and Knowledge Management in the context of Lean and describes Lean frameworks used for building the project steps of the practical part of this master thesis. Furthermore, an overview about current Lean practices in the company is provided. The practical part of this master thesis portrays the establishment and development of standards and Knowledge management in the Materials Management department. In details, the project steps are discussed and illustrated where applicable. Status update of the project is provided including the feedback of relevant stakeholders. Lastly, author gives recommendations for the further continuation of the project for the department from strategic, tactical and operational perspective.